Dampak Desentralisasi Fiskal terhadap Volatilitas Belanja Pemerintah Kabupaten/Kota di Indonesia - Mahi, B. Raksaka; Supriyanti, Syarah Siti (Jurnal Ekonomi dan Pembangunan Indonesia, 2019)
The volatility of expenditures sub-local derived from central government transparency in transfers to local governments may aggravate sublocal economy. This study aims to analyze the effect of fiscal decentralization to the level of volatility of local government spending in 230 sub-local in Indonesia. We use two periods, before and after the implementation of Law No. 28 Year 2009. The regression results indicate that the volatility of local government spending may decrease if the degree of fiscal decentralization increases, especially at the time when districts implement that law. As responsive taxation can provide incentives for smooth spending for sub-local government.